Integrating Islamic Tradition and Modern Education in the Madrasah Aliyah Curriculum: Strengthening Character Education in Pesantren - Madya, Suwarsih; Rafiah, Jihan Ariqatur; Ramadhani, Fitria Rembulan (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study explores the role of teachers in Islamic Boarding School-based Senior High Schools in curriculum integration, specifically how teachers understand and implement it, using a mixed-methods research design. In this case, the quantitative element consists of data collected through questionnaires (n=42), and the qualitative element consists of data collected through semi-structured interviews (n=8), classroom observations, and analysis of several relevant documents. The study uses descriptive statistics and thematic analysis to present the collected data. This study shows that teachers view integration as the unification of scientific knowledge with Islamic knowledge taught from the perspective of tawhid. While graduates of Islamic universities emphasize the formation of students' ethics and spirituality, graduates of public universities specifically focus on the pedagogical dimension of practice. Nonetheless, both groups of teachers contribute to promoting character education through examples, habits, and the learning context. Integration is carried out through religious worship, the moral integrity of teachers, and the Islamic approach to studying various subjects. On the contrary, its implementation is inconsistent, mainly due to a lack of individual initiative, a limited institutional framework, and the absence of systematic curriculum integration. The epistemology of Tauhidik Bakar in relation to the Tebuireng Islamic Boarding School, along with 'ta'dib Al-Attas, pedagogically describes the unification of knowledge, or the integration of Islamic knowledge systems in the process of moral formation. It demonstrates the ability of Islamic education to integrate moral development with epistemological coherence. It serves as a model for the construction of an inter-systemic curriculum of Islamic education that is balanced between 'ilm Ahl al-Kitab and al-Sunnah.